Dilemma of customary land policy in Indonesia - Aura Dian Marta; Utang Suwaryo; Affan Sulaeman; Leo Agustino (Masyarakat, Kebudayaan dan Politik, 2019)
Indonesia’s policy of customary land regulation does not eradicate the problems faced by indigenous people. Disputes over customary land proprietary rights continue to occur even in this current era of decentralization and democracy. Departing from empirical phenomena, this study aims to uncover customary land policy dilemmas and explore strategies to reconstruct customary land policies in Indonesia. This study uses a qualitative approach to literature study methods. This study was conducted in Indonesia and uses various cases of customary land policy from the provinces of Riau, East Kalimantan, and Papua. The data collected in this study is derived from books, documents, journals, research results, and news in electronic media. The results of the study show that Indonesia has a policy dilemma in the regulation of customary land for a number of reasons. First, customary land policies governed by customary law and national law often result in disputes. Second, in relation to natural resources management, there is no synchronization and harmony between sectoral laws and the Basic Principles of Agrarian Law (UUPA). Third, the government is yet to create policies at the local level regarding the protection and recognition of customary land. Therefore, the ideal strategy of policy reconstruction is to create a synergy between government institutions and all stakeholders in the policymaking process of customary land regulation. The conclusion of this study is that the policy dilemma of customary land in Indonesia will continue to occur if the government does not involve the participation of indigenous people and groups of interest in the policymaking process of customary land regulation.